2018
DOI: 10.1088/1361-648x/aae0a4
|View full text |Cite
|
Sign up to set email alerts
|

Variational study of the interacting, spinless Su–Schrieffer–Heeger model

Abstract: We study the phase diagram and the total polarization distribution of the Su-Schrieffer-Heeger model with nearest neighbor interaction in one dimension at half-filling. To obtain the ground state wave-function, we extend the Baeriswyl variational wave function to account for alternating hopping parameters. The ground state energies of the variational wave functions compare well to exact diagonalization results. For the case of uniform hopping for all bonds, where it is known that an ideal conductor to insulato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…with R(κ ) and κ bc defined in Eqs. (19) and (20). The pole contribution coincides with the negative edge state density at μ = 0.…”
Section: B Spectra and The Densitysupporting
confidence: 54%
See 1 more Smart Citation
“…with R(κ ) and κ bc defined in Eqs. (19) and (20). The pole contribution coincides with the negative edge state density at μ = 0.…”
Section: B Spectra and The Densitysupporting
confidence: 54%
“…However, in many respects this understanding relies on ideas which make explicit use of the concept of independent particles. Insights on the relation between topology and the physics of interacting many-body systems are based either on case studies for specific models or on general considerations of how to extend the concept of topological invariants to the realm of correlated systems [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Yoshida et al 32 showed a correlations-driven edge-Mott state with gapful charge and gapless spin excitations, which corresponds to the degeneracy of the entanglement spectrum of bulk. For the spinless SSH model, the correlation represented by the nearest neighbor Hubbard interaction was supposed to induce the charge density wave state (CDW) in the whole domain of the nearest neighbor hoppings 33 . However, the effects of correlations on the two-dimensional SSH model have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we apply a variational Monte Carlo [27] for strongly correlated bosonic models based on the Baeriswyl wavefunction [28][29][30][31][32][33][34] (BWF) and exact diagonalization (ED) to study the superfluid response and the polarization amplitude [35][36][37][38][39][40][41][42][43][44] of the one-dimensional BHM. Central to our study is the derivation of the expression for the superfluid weight valid in variational calculations, and emphasis of the role of interference between Peierls phases of particle paths in calculating the superfluid weight.…”
Section: Introductionmentioning
confidence: 99%